The impact of university students’ communication characteristics on team performance through entrepreneurial competencies - Hye-young, Ka; Sin-Bok, Lee (Edelweiss Applied Science and Technology, 2025)
This study investigates the impact of university students’ communication characteristics on team performance through entrepreneurial competencies. The research categorizes communication characteristics into clarity, interactivity, empathy, timeliness, and digital affinity, and examines their influence on entrepreneurial competencies, namely problem-solving, collaboration, and managerial knowledge. The study further explores how these competencies contribute to team performance. The findings reveal that clarity, interactivity, and empathy significantly enhance problem-solving and collaboration, leading to improved team performance. Specifically, clarity reduces misunderstandings and facilitates efficient teamwork by conveying information accurately. Interactivity fosters active feedback and idea exchange among team members, enabling practical and creative solutions. Empathy strengthens trust and emotional bonds within the team, creating a collaborative and supportive environment. However, timeliness and digital affinity did not show a significant effect on problem-solving or collaboration, indicating that merely fast communication or technological tool usage may not directly influence these processes. This research highlights the importance of developing communication characteristics and entrepreneurial competencies among university students and provides practical implications for educational strategies to enhance these capabilities and maximize team performance.